Misaligned feeding impairs memories - Loh, Dawn H; Jami, Shekib A; Flores, Richard E; Truong, Danny; Ghiani, Cristina A; O’Dell, Thomas J; Colwell, Christopher S (eLife, 2015)
Robust sleep/wake rhythms are important for health and cognitive function. Unfortunately, many people are living in an environment where their circadian system is challenged by inappropriate meal- or work-times. Here we scheduled food access to the sleep time and examined the impact on learning and memory in mice. Under these conditions, we demonstrate that the molecular clock in the master pacemaker, the suprachiasmatic nucleus (SCN), is unaltered while the molecular clock in the hippocampus is synchronized by the timing of food availability. This chronic circadian misalignment causes reduced hippocampal long term potentiation and total CREB expression. Importantly this mis-timed feeding resulted in dramatic deficits in hippocampal-dependent learning and memory. Our findings suggest that the timing of meals have far-reaching effects on hippocampal physiology and learned behaviour.
Keywords: learning and memory; hippocampus; circadian rhythm; CREB